2021
DOI: 10.31014/aior.1993.04.01.181
|View full text |Cite
|
Sign up to set email alerts
|

Entry Grades and the Academic Performance of University Students: A Review of Literature

Abstract: Universities world over mostly base their decisions to admit their new students on the applicant’s pre-university academic results. However, there is yet no concrete evidence that the students’ pre-university academic accolades determine their performances at university level. In this article, we explored the findings of earlier studies that examined the relationships between entry grades and the academic performance of university students. The study was undertaken to collate the literature on the relationship… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, universities' use of A-level performance as the primary criterion for admission to undergraduate degree programs has been subject to criticism. For example, a recent review by Aciro, Onen, Malinga, Ezati, and Openjuru (2021) identified positive, negative, and mixed correlations between entry grades and university students' exit academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, universities' use of A-level performance as the primary criterion for admission to undergraduate degree programs has been subject to criticism. For example, a recent review by Aciro, Onen, Malinga, Ezati, and Openjuru (2021) identified positive, negative, and mixed correlations between entry grades and university students' exit academic performance.…”
Section: Introductionmentioning
confidence: 99%